ANTIBACTERIAL EFFECTIVENESS OF BEETROOT AGAINST STREPTOCOCCUS MUTANS - Ulfa Yasmin; Ibnu Adjiedarmo; Yulia Christianti; Sulistiawati Sulistiawati; Mellani Cindera Negara (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Antibacterial effectiveness is the level of an antibacterial agent’s ability in controlling bacteria through growth-inhibiting or killing activities. A natural antibacterial agent that has the potential to be used as an alternative is beetroot (Beta vulgaris L.) because it contains phenolic compounds, flavonoids, saponins, tannins, and betalains. Antibacterial agents have been widely used as preventive for dental caries in children with the main causative bacteria being Streptococcus mutans. This study aims to evaluate the antibacterial effectiveness of beetroot extract against Streptococcus mutans. Methods: This study was in vitro experimental laboratory study with a post-test-only control group design. The maceration method used to obtain beetroot extract which will diluted into various concentrations, 12,500 μg/ml, 25,000 μg/ml, 50,000 μg/ml, and 100,000 μg/ml. Antibacterial effectiveness was tested by measuring the inhibition zone using disc diffusion, determining the Minimum Inhibitory Concentration (MIC) using broth dilution, and the Minimum Bactericidal Concentration (MBC) using agar dilution with 0,2% chlorhexidine gluconate as the positive control. Analysis of inhibition zone data was performed statistically using one-way ANOVA and Tukey Post Hoc. MIC and MBC tests were analyzed descriptively. Results: The results show all concentrations of beetroot extract were able to form an inhibition zone with the largest mean was 0.40 ± 0.05 mm, but still lower than the positive control. MIC and MBC of extract were 25,000 μg/ml and 50,000 μg/ml respectively. Conclusion: It can be concluded that beetroot extract has antibacterial effectiveness against Streptococcus mutans, therefore it can be used as a natural alternative for dental caries prevention.